Efficacy and safety of Bacillus clausii (O/C, N/R, SIN, T) probiotic combined with oral rehydration therapy (ORT) and zinc in acute diarrhea in children: a randomized, double-blind, placebo-controlled study in India - Keya Rani Lahiri; Raghvendra Singh; Mohini Apte; Mahantesh Patil; Amar Taksande; Rafael Varona; Godhuli Chatterjee; Manish Verma; Sandrine Brette; Marcos III Perez (Tropical Diseases, Travel Medicine and Vaccines, 2022)
Abstract Background Childhood diarrhea remains a major disease burden, particularly in developing countries, and is a leading cause of death in children aged < 5 years, worldwide. Treatment of acute diarrhea now includes probiotics to potentially reduce the duration and severity of the illness. This phase 3, randomized, placebo-controlled, double-blind study assessed the efficacy and safety of four strains (O/C, N/R, SIN, T) of Bacillus clausii probiotic (Enterogermina®) plus oral rehydration therapy (ORT) and zinc, versus placebo plus ORT and zinc, in infants and children in India with acute moderate diarrhea. Methods Patients aged 6 months to 5 years with acute moderate diarrhea (WHO 2005 definition) of < 48 h’ duration were randomly assigned to receive one mini bottle of either polyantibiotic-resistant B. clausii (oral suspension of 2 billion spores per 5 mL bottle) or matching placebo twice daily (morning and evening) for 5 days. Exclusion criteria included known hypersensitivity to B. clausii or excipients in the study treatment, or to other probiotics. Patients were admitted to hospital from Day 1 and discharged ≥6 h after diarrhea resolution, or a maximum of 5 days. The primary endpoint was duration of acute diarrhea from randomization to recovery. Secondary endpoints included frequency of stools, diapers with stools, or dehydration status. Results In total, 457 patients were randomized; 454 were treated. Similar proportions of patients showed recovery from diarrhea over the 120 h after randomization (97.0% in the B. clausii group [n = 227]; 98.0% on placebo [n = 227]). Median time to recovery was also similar: 42.83 (95% CI: 40.90–44.90) hours for B. clausii and 42.13 (95% CI: 39.80–43.87) hours for placebo. However, no statistically significant difference was observed between groups (hazard ratio = 0.93 [95% CI: 0.77–1.13]; p = 0.6968); nor were there statistically significant differences between groups for the secondary endpoints. Treatment with B. clausii was well tolerated with incidence of ...